1987
DOI: 10.1007/bf01020537
|View full text |Cite
|
Sign up to set email alerts
|

Differences in attraction to semiochemicals present in sympatric pine shoot beetles,Tomicus minor andT. piniperda

Abstract: Abstract--The chemical ecology of host-and mate-finding in the pine shoot beetles, Tomicus minor and T. piniperda, was studied in southern Sweden. Beetles were collected in the field from defined attack phases on Scots pine. Using gas chromatography-mass spectroscopy, a number of oxygen-containing monoterpenes, e.g., 3-carene-10-ol, myrtenol, trans-verbenol, and verbenone, were identified from hindgut extracts of both sexes of both species. Compared to T. minor, T. piniperda contained additional compounds and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 31 publications
2
81
1
1
Order By: Relevance
“…Lanne et al (1987) showed compounds not found in T. piniperda (exo-brevicomin, ipsenol, and pheromone components of other bark beetle species) elicited an EAG response in the beetle. Some of these compounds are found in competing species of bark beetles, but other compounds are probably found only in species colonizing nonhost trees (e.g., Norway spruce).…”
Section: Sensory Organsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lanne et al (1987) showed compounds not found in T. piniperda (exo-brevicomin, ipsenol, and pheromone components of other bark beetle species) elicited an EAG response in the beetle. Some of these compounds are found in competing species of bark beetles, but other compounds are probably found only in species colonizing nonhost trees (e.g., Norway spruce).…”
Section: Sensory Organsmentioning
confidence: 99%
“…Observations of I. paraconfisus, I . typographus, D. brevicomis, P. chalcographus, and T. piniperda in flight chambers under dim red light or in complete darkness using an electronic vibration detector indicate they will not fly after dark (Lanne et al, 1987;Byers and Lofqvist, 1989;Byers, unpublished). Bark beetles are attracted more so to traps baited with host odor or pheromone that are placed next to tree trunk silhouettes than to traps without such visual stimuli, indicating that beetles orient to the tree hunk during landing (Moser and Browne, 1978;Borden et al, 1982;Tilden et al, 1983;Lindgren et al, 1983;Bombosch et al, 1985;Ramisch, 1986; ChCnier and Philogbne, 1989).…”
Section: Sensory Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another disadvantage is that some insects such as locusts (Blaney and Simmonds, 1990) and bark beetles (Dickens et al, 1985;Lanne et al, 1987) contain either many generalist receptors or (more likely) many different kinds of more specialized receptors, since many chemicals elicit voltage potentials in the electroantennogram. This makes it more difficult to determine the importance of candidate chemicals to a specific behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the release rate should parallel the expected or measured rates of natural release (Byers et al, 1985). Usually, however, a range of rates that are expected to overlap the natural rate are used (Schlyter et al, 1987;Byers et al, 1988). As the release rate is increased, there is a point when activity begins (e.g., catch increases above the control), and this rate is assumed to be similar to the natural one.…”
Section: Discussionmentioning
confidence: 99%